Protein folding and misfolding: from theory to therapy - Dobson, Christopher (Henry Stewart Talks, 2007)
Protein nature, folding and complexity, Folding in a cellular environment, The underlying principles of folding, Native and transition states, Exploring the energy surface, The folding of lysozyme, The consequences of protein misfolding, The relationship between folding and disease, Protein deposition diseases, Protein aggregates in amyloid diseases, Amyloidogenic mutations of lysozyme, Mechanism of amyloid formation, Structure of the amyloidogenic intermediate, Amyloid formation by lysozyme in vivo, SH3 domain of PI3 kinase, Model of an amyloid fibril, The underlying origins of amyloid disease, Generic toxicity of amyloid aggregates, Cellular defences against aggregation, Evolutionary design of proteins, "Post-evolutionary" diseases